Sustained, job-embedded professional development and the learning environment of middle-level mathematics classrooms - Gabler, Craig Thomas (Curtin University, 2007)
As the need for educational reform is increasingly recognized, so too is the need for effective professional development (Guskey, 2000). Historically the evaluation of professional development experiences has been limited to exit surveys, noticeably failing to examine the long-term impact of the effort. This study assessed the impact on the classroom learning environment of a yearlong, job-embedded professional development opportunity for middle-school mathematics teachers. The application of learning environment instruments to the evaluation of professional development is a unique feature of this study. The research employed the Questionnaire on Teacher Interactions (QTI) and a modified version of the What Is Happening In this Class? (WillIC) survey with over 1000 middle-school mathematics students in 57 classrooms in the state of Washington. Both instruments were administered at the beginning and end of the school year. Teacher interviews were conducted with a sample of participants in order to further illuminate the impact of the professional development. Data from the study were examined for changes in the learning environment and to cross-validate the QTI and WIHIC with this specific population. Results indicate that the QTI and WIHIC are valid and reliable with the middle-school population is this study. Statistical analyses of learning environment data indicate that any pretest-posttest changes that were observed are mostly likely too small to be of educational significance. This study contributes to a better general understanding of the impact of this professional development, and its findings could be utilized in the preparation of future professional development opportunities.